Electronic devices electron flow version - Floyd, Thomas L. (Prentice Hall, 2012)
Electronic Devices (ELECTRON FLOW VERSION) , Ninth Edition, provides a solid foundation in basic analog electronics and a thorough introduction to analog integrated circuits and programmable devices. The text identifies the circuits and components within a system, helping students see how the circuit relates to the overall system function. Full-color photos and illustrations and easy-to-follow worked examples support the text's strong emphasis on real-world application and troubleshooting. Updated throughout, the ninth edition features new GreenTech Applications and a new chapter, "Basic Programming Concepts for Automated Testing."